Descrição de novos materiais de Massetognathus ochagaviae barberena, 1981 (cynodontia, traversodontidae) para o triássico do Sul do Brasil, com ênfase no esqueleto pós-craniano - Pavanatto, Ane Elise Branco (2015)
This dissertation provides information on new material (UNIPAMPA 0625) assigned to Massetognathus ochagaviae, with emphasis in the description of its postcranial material. UNIPAMPA 0625 was collected at the municipality of Dona Francisca (Sítio Fogliarini/Posto de Gasolina). Its assignation to M. ochagaviae was basedon the upper postcaninemorphology. Posteriorly, this previous assignation was supported by a phylogenetic analysis in which the new specimen was included. The material comprises a single incisive tooth, four upper and lower isolated postcanines, an isolated fragmentary portion of a skull comprising a jugal and a lacrimal, nine presacral and four sacral vertebrae, a single caudal vertebra, fragmentary presacral ribs, an incomplete left scapula, left clavicle, both right and left humeri, left radium, left ilium, left ischium, both right and left femora and several undetermined and fragmentary bones. The postcranial morphology of M. ochagaviae is quite similar to that of Massetognathus pascuali, especially regarding vertebrae, the morphology of the transverse process; humeri, (dorsally deflected head, with a „fan-shaped‟ distal end; deltopectoral crest that abruptly ends at the middle of shaft); and femora (a bulbous and dorsomedially inclined femoral head; lesser trochanter which abruptly begins near by the intertrochanteric fossa and extends until the middle of the femoral shaft; the medial condyle is more pronounced and ventrally projected than the lateral one). On the other hand, the clavicle of M. ochagaviae is less elongated than in M. pasquali. Also, the dorsal margin of the ilium is not as concave as in M. pascuali. The description of the material herein presented filled a long-term gap in the kwonledge regarding the skeletal material of M. ochagaviae, and increasing the kwonledge not only regarding this taxon, but of traversodontids as well.